Risk Management in Work Activities at Ammonia Plant Fertilizer Production Industry - Dhea Rizky Novandhini; M. Affan Mahfudz; Indriati Paskarini (Universitas Airlangga, 2020)
Introduction: PT X is one of the companies in fertilizer production industry. There are two high-risk activities that endanger the safety and health of workers, namely supervision of welding and oil level checking in ammonia plant field of PT X. The purpose of this research was to apply risk management to the activities. Method: This research was a descriptive study which was carried out in observation using a cross sectional design. Variables in this study included hazard identification, basic risk analysis, risk control that has been done, existing risk analysis, and risk reduction assessment. The tools used for the data collection were observation sheets, interview guide sheets, and Job Safety Analysis sheets. Data that has been obtained through observation and interviews was processed using Fine (1971) semi quantitative technique. Results: The results of hazard identification were known to have as many as 6 potential hazards. The assessment results in the basic risk analysis showed that the initial risk level consisted of 3 risks with very high level, 2 risks with a substantial level and 1 risk with priority 3 level. After the risk control effort was applied, the results of the assessment in the existing risk analysis showed that the level of risk has decreased significantly. Conclusion: The value of risk reduction of each potential hazard results decreases by 95%, 88.89%, 85%, 93.33%, 66.67%, and 75%.Keywords: ammonia plant, fertilizer production industry, risk management